Variational Analysis of the Speed of Propagating Fronts in Superconductors (The Chittagong University Journal of Science, 2022)
A new approach has taken to determine the speed of the superconducting-normal interface (front) propagating from a stable superconducting phase to the unstable normal phase by means of a variational method. In this process a trial function g(x) is introduced which has a relation with the superconducting order parameter F. Starting from the time-dependent Ginzburg-Landau (TDGL) equations an expression is derived for the front speed in terms of GL parameter κ.The Chittagong Univ. J. Sci. 43(1): 41-50, 2021